AKTIVASI SPONTAN SEL T LIMFOSIT MENCIT YANG MENGALAMI DEFISIENSI IL2Rβ - Endharti, Agustina Tri (Fakultas Kedokteran Universitas Brawijaya, 2007)
Homologous recombination applied to alter specific endogenous gene, referred as gene targeting, provides the highest level of control over product mutation in cloned genes. In this experiment we showed that by using gene targeting a knock out mutation in IL-2Rβ gene could be generated. The findings of this study indicated that mice lacking the Interleukin-2 receptor β chain (IL2Rβ-/-) had spontaneously activated.T cells. In this study, we investigated abnormal expansion of activated T cells which showed high level of CD69. These findings suggest that the IL2Rβ-/- mice may serve as animal model for autoimmune diseases and that the accumulation of activated T cell in the future could be usedin clinical setting to cure the diseases. Keywords:T cells, (IL2Rβ-/-), autoimmune